Good to share? The pecuniary implications of moving to shared service production for local government services. (8th February 2019) - Drew, Joseph; McQuestin, Dana; Dollery, Brian E.
Abstract : Shared services are often lauded as an efficacious means of reducing municipal expenditure and thereby improving waning financial sustainability. However, most of the extant theoretical and empirical work only considers costs and benefits at the level of the specific service in question and, hence, fails to capture many of the wider benefits and costs that might accrue to local governments. In this article we first build a schema to illustrate the benefits and costs of moving from separate to collaborative production at the level of individual local authorities. We then test two hypotheses drawn from the schema against a five‐year panel of expenditure data. We find evidence of increased expenditure in the order of 8 per cent that prima facie runs counter to the objectives of many municipal managers engaged with shared services. We conclude by considering the implications of our findings for cooperative ventures between local authorities.